The Intricate Justice of Poverty: A Case of The Land of Gold in Papua Indonesia (Journal of Indonesian Legal Studies, 2022)
Natural wealth does not guarantee the welfare of its inhabitants. This case occurred in Papua, the easternmost region of Indonesia, which won the title of the poorest province from 2017 to 2021. Freeport McMoRan, an American mining corporation operating since 1967, failed to present a positive impact on the welfare of the Papuan people despite having dredged a lot of money from Grasberg, one of the largest reserves of gold and copper in the world. This paper reviews the portrait of abject poverty in Papua and analyzes its problems with the rights and justice approach. In conclusion, this paper finds that poverty for the Papuan people is very complicated because it is related to the historical roots of colonialism, capitalism, and armed conflicts. The special autonomy granted by the Indonesian government for twenty years has not been able to provide for people's welfare due to violent conflicts, human rights violations, natural destruction, and corruption. The Indonesian government is obliged to realize justice in the economic, political, and cultural dimensions for the welfare of the Papuan people.